Pathways to developing information technology-enabled capabilities in born-digital new ventures. (February 2023) - Sadreddin, Arman; Chan, Yolande E.
Abstract: Despite significant business opportunities made possible through advancements in technology, readily available digital technologies are often overlooked and not used by new ventures. To address this knowledge gap, this paper looks at the relationships between readily available digital technologies and born-digital new venture capabilities. We use an affordance lens to explore conditions in which born-digital new ventures interact with digital technologies to actualize digital affordances that facilitate the development of important capabilities. First, using the existing literature, we present a research model and its key elements. Then, using data on new ventures in a Canadian university incubator, we conduct fuzzy-set qualitative comparative analysis (fsQCA) and develop seven configurational research propositions as pathways to develop information technology-enabled organizational capabilities in new ventures. Using this retroductive approach, this research builds a context-specific middle-range theory that explains complex interactions between readily available digital technologies and new venture characteristics, where resources are provided by incubators in dynamic environments, to facilitate the development of ITOCs in the new ventures. We close by describing the study's theoretical and practical implications. Highlights: Explaining how new ventures develop IT-enabled organizational capabilities. Developing a context-specific middle-range theory using retroduction and fsQCA. Highlighting the importance of technology affordances in entrepreneurial ecosystems. Examining the role of digital technology in academic entrepreneurship settings. Guiding policy on strategic IT investments in entrepreneurial ecosystems.